2009
DOI: 10.1073/pnas.0905117106
|View full text |Cite
|
Sign up to set email alerts
|

Polar firn air reveals large-scale impact of anthropogenic mercury emissions during the 1970s

Abstract: Mercury (Hg) is an extremely toxic pollutant, and its biogeochemical cycle has been perturbed by anthropogenic emissions during recent centuries. In the atmosphere, gaseous elemental mercury (GEM; Hg°) is the predominant form of mercury (up to 95%). Here we report the evolution of atmospheric levels of GEM in mid-to high-northern latitudes inferred from the interstitial air of firn (perennial snowpack) at Summit, Greenland. GEM concentrations increased rapidly after World War II from Ϸ1.5 ng m ؊3 reaching a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 62 publications
9
65
0
Order By: Relevance
“…The sediment, peat, and ice core studies suggest that the mercury deposition peaked between 1950 and 1990 at a majority of sites (Schuster et al, 2002;Biester et al, 2007;Muir et al, 2009;Mast et al, 2010), although it is still increasing at some locations (Fitzgerald et al, 2005). The firn study by Fain et al (2009) suggests that the mercury concentration in air peaked at around 1970. The decreasing emissions from the legacy of historical mercury use and emissions thus appear to be the most plausible explanation for the observed trend.…”
Section: Resultsmentioning
confidence: 99%
“…The sediment, peat, and ice core studies suggest that the mercury deposition peaked between 1950 and 1990 at a majority of sites (Schuster et al, 2002;Biester et al, 2007;Muir et al, 2009;Mast et al, 2010), although it is still increasing at some locations (Fitzgerald et al, 2005). The firn study by Fain et al (2009) suggests that the mercury concentration in air peaked at around 1970. The decreasing emissions from the legacy of historical mercury use and emissions thus appear to be the most plausible explanation for the observed trend.…”
Section: Resultsmentioning
confidence: 99%
“…In order to retrieve a history of atmospheric Hg 0 at middle and high northern latitudes, Hg 0 was measured in the interstitial air of firn (perennial snowpack) in the Greenland icecap. From this record, it has been shown that anthropogenic emissions caused a two-fold increase in boreal atmospheric Hg 0 concentrations before the 1970s, which possibly contributed to higher deposition rates of mercury both in industrialized and remote areas (Faïn et al, 2008(Faïn et al, , 2009.…”
Section: F Sprovieri Et Al: a Review Of Worldwide Atmospheric Mercumentioning
confidence: 99%
“…Snowpack ventilation can, depending on the snowpack's permeability and the strength of the ventilation-driving turbulence (Kuhn, 2001;Albert and Shultz, 2002;Domine et al, 2008), extend to depths of 50-100 cm (Domine et al, 2008). Molecular diffusion, which is active at even greater depths (Faïn et al, 2009), continuously transfers mercury vertically.…”
Section: Snowpack/meltwater Modelmentioning
confidence: 99%
“…Faïn et al (2009) used a diffusion model to deduce atmospheric GEM concentrations from 1940 to 2006 from concentrations of GEM in firn air. Poulain et al (2007b) presented a mass balance for mercury in snowpacks that considered wet and dry depositions and throughfall as sources and revolatilization and snowmelt as sinks.…”
Section: Durnford Et Al: Modelling the Fate Of Mercury Deposited mentioning
confidence: 99%